Trends in the application of high-resolution mass spectrometry for human biomonitoring: An analytical primer to studying the environmental chemical space of the human exposome. (March 2017) - Andra, Syam S.; Austin, Christine; Patel, Dhavalkumar; Dolios, Georgia; Awawda, Mahmoud; Arora, Manish
Abstract: Global profiling of xenobiotics in human matrices in an untargeted mode is gaining attention for studying the environmental chemical space of the human exposome. Defined as the study of a comprehensive inclusion of environmental influences and associated biological responses, human exposome science is currently evolving out of the metabolomics science. In analogy to the latter, the development and applications of high resolution mass spectrometry (HRMS) has shown potential and promise to greatly expand our ability to capture the broad spectrum of environmental chemicals in exposome studies. HRMS can perform both untargeted and targeted analysis because of its capability of full- and/or tandem-mass spectrum acquisition at high mass accuracy with good sensitivity. The collected data from target, suspect and non-target screening can be used not only for the identification of environmental chemical contaminants in human matrices prospectively but also retrospectively. This review covers recent trends and advances in this field. We focus on advances and applications of HRMS in human biomonitoring studies, and data acquisition and mining. The acquired insights provide stepping stones to improve understanding of the human exposome by applying HRMS, and the challenges and prospects for future research. Graphical abstract: Highlights: Human biomonitoring is limited by the number of chemicals analyzed in a targeted approach. High resolution mass spectrometry (HRMS) can monitor a broad-spectrum of exposure and biological response markers. Advances in data acquisition workflows accelerate untargeted profiling of the human exposome environmental chemical space. Intelligent data mining filters and tools are constantly evolving to characterize unknown compounds. High throughput simultaneous identification and quantitation of new chemicals and metabolites will be feasible with HRMS.